2021
DOI: 10.3390/ijerph18052715
|View full text |Cite
|
Sign up to set email alerts
|

Impact of School-Based Oral Health Education on Vietnamese Adolescents: A 6-Month Study

Abstract: We have evaluated the impact of a school-based intervention on oral health knowledge, behaviours, and oral health status of adolescents in Vietnam. This 6-month study included 462 adolescents aged 12 years from four selected schools in Hue City, Vietnam. The intervention group received a 15-min lecture by a dentist and hands-on session on mouth observation and toothbrushing skills. The control group did not engage in any educational activities during the follow-up period. Data were collected at baseline and 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 44 publications
2
13
0
2
Order By: Relevance
“…El estudio con mayor efectividad fue el realizado en Magway, esto porque la promoción de salud fue realizada durante un año, con promoción de salud impartida cada ocho semanas a los escolares (Nguyen et al, 2021).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…El estudio con mayor efectividad fue el realizado en Magway, esto porque la promoción de salud fue realizada durante un año, con promoción de salud impartida cada ocho semanas a los escolares (Nguyen et al, 2021).…”
Section: Discussionunclassified
“…En un estudio realizado en Vietnam, al igual que el estudio realizado en Madway y Hong Kong, se dividieron las escuelas en grupos; en el grupo intervención se realizó promoción de salud bucodental, mediante una presentación en PowerPoint. En cambio, en el grupo control, no se realizó promoción de salud, y como resultado se obtuvo que la promoción de salud en el grupo intervención reportó una mejora en el cepillado de dientes y la higiene bucal a corto plazo, pero esto no impidió que se sigan desarrollando caries en los escolares a largo plazo; el grupo control mostró nula eficacia sobre la mejora de salud bucodental (Nguyen et al, 2021).…”
Section: Materiales Y Métodosunclassified
“…OHE for schoolchildren is a widely adopted primary strategy for the prevention of oral diseases, owing to its cost-effectiveness and simplicity in administration [ 14 , 15 ]. Studies have demonstrated that cartoon-animated audiovisual aids and game-based education implemented for schoolchildren are powerful tools for educating and providing thought-stimulating methods of learning [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The period of transition from childhood to adulthood is associated with many changes, including physical, sexual, and psycho-social changes, and in this period, unfortunately, neglecting health care, including oral health care, has become commonplace [11,12). In this period, independence from parents increases and leads to behavior changes, including behaviors related to eating habits, smoking, health behaviors, and lifestyle, and these independent behaviors can affect oral health and patterns Create a lifelong habit [13].…”
Section: Introductionmentioning
confidence: 99%